Germany : Financial Sector Assessment Program-Insurance Sector Supervision-Technical Notes. (IMF Staff Country Reports; Country Report, 2016)
This paper provides an update on the German insurance sector and an analysis of certain key aspects of the regulatory and supervisory regime. It includes an analysis of German practice in relation to selected Insurance Core Principles in the context of a wider discussion of key issues in regulation and supervision. This technical note focuses mainly on recent developments in the sector and key vulnerabilities, including life insurance issues, those vulnerabilities associated with the continuing low interest rate environment; the preparations of the authorities and industry for the implementation of the Solvency II requirements; and the supervisory approach to large insurance groups.